Pengaruh Current Ratio dan Debt To Equity Ratio Terhadap Return On Equity (Studi Kasus pada Perusahaan Otomotif & Komponen yang Terdaftar di BEI Tahun 2019-2022) - Syahra, Jihan Shafa Nur; Maula, Kholida Atiyatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on Return on Equity in automotive and component companies listed on the IDX in 2019-2022. The sample in this study used purposive sampling method with the number of samples selected as many as 8 companies from a population of 10 companies. The technique used uses the classic assumption test and multiple linear regression analysis. The results showed that the Current Ratio t test had a value of (0.467) < (2.04523) the significance value (0.644> 0.05) had no effect on Return on Equity, the Debt to Equity Ratio t test (0.093) < (2.04523) the significance value (0.927> 0.05) had no effect on Return on Equity, and the F test (0.119) < (3.33) with significance (0.888> 0.05) so that together Current Ratio, Debt Equity Ratio has no effect on Return on Equity.